2021
DOI: 10.1039/d1ra00682g
|View full text |Cite
|
Sign up to set email alerts
|

Achieving the potential multifunctional near-infrared materials Ca3In2−xGaxGe3O12:Cr3+using a solid state method

Abstract: Near-infrared spectroscopy is developing rapidly in the fields of human detection and food analysis due to its fast response and non-invasive characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 51 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…Ca 3 Ga 2 Ge 3 O 12 :Cr 3+ has three centered emission peaks at 749, 803, and 907 nm, while Ca 3 In 2 Ge 3 O 12 :Cr 3+ also possesses two distinct luminescent centers at 810 and 900 nm. 36,37 Mg 3 Y 2 Ge 3 O 12 also possesses three luminescent centers at 748, 806, and 899 nm. 38 It is assumed that the broadband NIR luminescence in germanate is due to the occupation of Cr 3+ in both the dodecahedral and octahedral environments.…”
Section: Classification Of Garnet Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 3 Ga 2 Ge 3 O 12 :Cr 3+ has three centered emission peaks at 749, 803, and 907 nm, while Ca 3 In 2 Ge 3 O 12 :Cr 3+ also possesses two distinct luminescent centers at 810 and 900 nm. 36,37 Mg 3 Y 2 Ge 3 O 12 also possesses three luminescent centers at 748, 806, and 899 nm. 38 It is assumed that the broadband NIR luminescence in germanate is due to the occupation of Cr 3+ in both the dodecahedral and octahedral environments.…”
Section: Classification Of Garnet Systemsmentioning
confidence: 99%
“…46 At high temperatures, phosphor photoluminescence can be thermally quenched via thermal activation or thermal ionization mechanisms. 37 Thermal activation occurs when electrons in the excited state increasingly vibrate at high temperatures and cross the potential barrier between the ground and excited states, resulting in nonradiative relaxation to the ground state. The difference in energy between 2 E g and/or 4 T 2g and 4 A 2g influences thermal activation and is commonly represented as activation energy (DE).…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…According to Dexter's energy transfer theory, θ = 6 corresponds to electric dipole-dipole interactions, whereas θ = 3 represents the energy transfer among the nearest or next-nearest Cr 3+ activators. 38,39 Therefore, the concentration quenching mechanism in RNYF:Cr is presumably attributed to the energy transfer between the nearest or nextnearest Cr 3+ activators. The spectra shown in Fig.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…They can absorb NIR light and convert the inorganic salts in the environment into amino acids and nucleotides that are easy for plants to absorb, thus promoting the biological nitrogen fixation of plants and promoting plant growth. 5 In addition, it is found that when red and deep-red light are irradiated together, the growth rate of plants is much greater than the sum of their respective irradiation rates, which is known as the Emerson effect. 6 PC-LED, a combination of phosphors and LED chips, has promoted the development of lighting technology.…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetic bacteria, which are widely found in soil, play an important role in plant growth, especially in roots. They can absorb NIR light and convert the inorganic salts in the environment into amino acids and nucleotides that are easy for plants to absorb, thus promoting the biological nitrogen fixation of plants and promoting plant growth . In addition, it is found that when red and deep-red light are irradiated together, the growth rate of plants is much greater than the sum of their respective irradiation rates, which is known as the Emerson effect …”
Section: Introductionmentioning
confidence: 99%